Exploring the antecedents and outcomes of destination brand love - Amaro, Suzanne (2021)
Purpose This study aims to apply the concept of brand love to a destination and investigate its antecedents and consequences. It also explores the moderating effects of time elapsed since the establishment of the destination brand love relationship on the outcomes of destination brand love. Design/methodology/approach A total of 5,511 valid responses were obtained from an online survey distributed among former international students from the Erasmus program of the European Union. Partial least squares structural equation modeling was conducted to assess the hypotheses. Findings Destination brand love was found to have a significant impact on electronic word of mouth (eWOM), WOM, WOM intensity, recommendation and revisit intention. Moderation analysis revealed that the amount of time elapsed since the establishment of the destination brand love relationship did not affect these outcomes. Moreover, destination image and the Erasmus experience had a positive effect on destination brand love. Practical implications Destination marketers should focus on enhancing the Erasmus experience and on improving destination image perception, as these factors help develop destination brand love. Marketers should also be aware that this relationship has long-lasting effects. Originality/value This study adds to the sparse literature on brand love in relation to a destination. This gives the first results for the importance of Erasmus students to the promotion of a host country. It also contributes to the question of how long the brand love relationship can last.